Citizen participation in public management processes, Puno Case, Peru - Adderly Mamani-Flores; Duverly Joao Incacutipa-Limachi; Alfredo Calderón-Torres; E Calatayud; Jorge Apaza-Ticona; Rulli William Incaluque-Sortija; Jaime Huaracha-Velasquez (My University, 2024)
In crisis situations, it is essential to increase representative democracy by structuring communities as tools to encourage citizen participation. For this reason, the research aimed to understand the reality of citizens and the processes of citizen participation mechanisms during the national crisis. It was a qualitative study that was based on phenomenological hermeneutics and identified six community leaders who are social actors in the city of Puno. The results demonstrated that the role of the community leader as an expression of the emotions of all citizens and the importance of community organization as a means of citizen participation are crucial to advance towards the construction of a strong and popular democracy. In conclusion, it is essential to have citizen participation mechanisms in times of crisis, as they allow communities that have traditionally been neglected to be heard and given a voice.
Keywords: Geography; Political science; Environmental planning; Environmental protection; Geography; Political science; Environmental planning; Environmental protection; Social Sciences Social Sciences Political Science and International Relations Public Policy and Governance; Social Sciences Business, Management and Accounting Organizational Behavior and Human Resource Management Educational and Organizational Development; Social Sciences Social Sciences Law Social Issues and Policies in Latin America